src/HOL/Library/Normalized_Fraction.thy
changeset 65417 fc41a5650fb1
parent 65416 f707dbcf11e3
child 65418 c821f1f3d92d
child 65419 457e4fbed731
--- a/src/HOL/Library/Normalized_Fraction.thy	Thu Apr 06 08:33:37 2017 +0200
+++ /dev/null	Thu Jan 01 00:00:00 1970 +0000
@@ -1,338 +0,0 @@
-(*  Title:      HOL/Library/Normalized_Fraction.thy
-    Author:     Manuel Eberl
-*)
-
-theory Normalized_Fraction
-imports 
-  Main 
-  "~~/src/HOL/Number_Theory/Euclidean_Algorithm" 
-  Fraction_Field
-begin
-
-definition quot_to_fract :: "'a :: {idom} \<times> 'a \<Rightarrow> 'a fract" where
-  "quot_to_fract = (\<lambda>(a,b). Fraction_Field.Fract a b)"
-
-definition normalize_quot :: "'a :: {ring_gcd,idom_divide} \<times> 'a \<Rightarrow> 'a \<times> 'a" where
-  "normalize_quot = 
-     (\<lambda>(a,b). if b = 0 then (0,1) else let d = gcd a b * unit_factor b in (a div d, b div d))" 
-
-definition normalized_fracts :: "('a :: {ring_gcd,idom_divide} \<times> 'a) set" where
-  "normalized_fracts = {(a,b). coprime a b \<and> unit_factor b = 1}"
-  
-lemma not_normalized_fracts_0_denom [simp]: "(a, 0) \<notin> normalized_fracts"
-  by (auto simp: normalized_fracts_def)
-
-lemma unit_factor_snd_normalize_quot [simp]:
-  "unit_factor (snd (normalize_quot x)) = 1"
-  by (simp add: normalize_quot_def case_prod_unfold Let_def dvd_unit_factor_div
-                mult_unit_dvd_iff unit_factor_mult unit_factor_gcd)
-  
-lemma snd_normalize_quot_nonzero [simp]: "snd (normalize_quot x) \<noteq> 0"
-  using unit_factor_snd_normalize_quot[of x] 
-  by (auto simp del: unit_factor_snd_normalize_quot)
-  
-lemma normalize_quot_aux:
-  fixes a b
-  assumes "b \<noteq> 0"
-  defines "d \<equiv> gcd a b * unit_factor b"
-  shows   "a = fst (normalize_quot (a,b)) * d" "b = snd (normalize_quot (a,b)) * d"
-          "d dvd a" "d dvd b" "d \<noteq> 0"
-proof -
-  from assms show "d dvd a" "d dvd b"
-    by (simp_all add: d_def mult_unit_dvd_iff)
-  thus "a = fst (normalize_quot (a,b)) * d" "b = snd (normalize_quot (a,b)) * d" "d \<noteq> 0"
-    by (auto simp: normalize_quot_def Let_def d_def \<open>b \<noteq> 0\<close>)
-qed
-
-lemma normalize_quotE:
-  assumes "b \<noteq> 0"
-  obtains d where "a = fst (normalize_quot (a,b)) * d" "b = snd (normalize_quot (a,b)) * d"
-                  "d dvd a" "d dvd b" "d \<noteq> 0"
-  using that[OF normalize_quot_aux[OF assms]] .
-  
-lemma normalize_quotE':
-  assumes "snd x \<noteq> 0"
-  obtains d where "fst x = fst (normalize_quot x) * d" "snd x = snd (normalize_quot x) * d"
-                  "d dvd fst x" "d dvd snd x" "d \<noteq> 0"
-proof -
-  from normalize_quotE[OF assms, of "fst x"] guess d .
-  from this show ?thesis unfolding prod.collapse by (intro that[of d])
-qed
-  
-lemma coprime_normalize_quot:
-  "coprime (fst (normalize_quot x)) (snd (normalize_quot x))"
-  by (simp add: normalize_quot_def case_prod_unfold Let_def
-        div_mult_unit2 gcd_div_unit1 gcd_div_unit2 div_gcd_coprime)
-
-lemma normalize_quot_in_normalized_fracts [simp]: "normalize_quot x \<in> normalized_fracts"
-  by (simp add: normalized_fracts_def coprime_normalize_quot case_prod_unfold)
-
-lemma normalize_quot_eq_iff:
-  assumes "b \<noteq> 0" "d \<noteq> 0"
-  shows   "normalize_quot (a,b) = normalize_quot (c,d) \<longleftrightarrow> a * d = b * c"
-proof -
-  define x y where "x = normalize_quot (a,b)" and "y = normalize_quot (c,d)" 
-  from normalize_quotE[OF assms(1), of a] normalize_quotE[OF assms(2), of c]
-    obtain d1 d2 
-      where "a = fst x * d1" "b = snd x * d1" "c = fst y * d2" "d = snd y * d2" "d1 \<noteq> 0" "d2 \<noteq> 0"
-    unfolding x_def y_def by metis
-  hence "a * d = b * c \<longleftrightarrow> fst x * snd y = snd x * fst y" by simp
-  also have "\<dots> \<longleftrightarrow> fst x = fst y \<and> snd x = snd y"
-    by (intro coprime_crossproduct') (simp_all add: x_def y_def coprime_normalize_quot)
-  also have "\<dots> \<longleftrightarrow> x = y" using prod_eqI by blast
-  finally show "x = y \<longleftrightarrow> a * d = b * c" ..
-qed
-
-lemma normalize_quot_eq_iff':
-  assumes "snd x \<noteq> 0" "snd y \<noteq> 0"
-  shows   "normalize_quot x = normalize_quot y \<longleftrightarrow> fst x * snd y = snd x * fst y"
-  using assms by (cases x, cases y, hypsubst) (subst normalize_quot_eq_iff, simp_all)
-
-lemma normalize_quot_id: "x \<in> normalized_fracts \<Longrightarrow> normalize_quot x = x"
-  by (auto simp: normalized_fracts_def normalize_quot_def case_prod_unfold)
-
-lemma normalize_quot_idem [simp]: "normalize_quot (normalize_quot x) = normalize_quot x"
-  by (rule normalize_quot_id) simp_all
-
-lemma fractrel_iff_normalize_quot_eq:
-  "fractrel x y \<longleftrightarrow> normalize_quot x = normalize_quot y \<and> snd x \<noteq> 0 \<and> snd y \<noteq> 0"
-  by (cases x, cases y) (auto simp: fractrel_def normalize_quot_eq_iff)
-  
-lemma fractrel_normalize_quot_left:
-  assumes "snd x \<noteq> 0"
-  shows   "fractrel (normalize_quot x) y \<longleftrightarrow> fractrel x y"
-  using assms by (subst (1 2) fractrel_iff_normalize_quot_eq) auto
-
-lemma fractrel_normalize_quot_right:
-  assumes "snd x \<noteq> 0"
-  shows   "fractrel y (normalize_quot x) \<longleftrightarrow> fractrel y x"
-  using assms by (subst (1 2) fractrel_iff_normalize_quot_eq) auto
-
-  
-lift_definition quot_of_fract :: "'a :: {ring_gcd,idom_divide} fract \<Rightarrow> 'a \<times> 'a" 
-    is normalize_quot
-  by (subst (asm) fractrel_iff_normalize_quot_eq) simp_all
-  
-lemma quot_to_fract_quot_of_fract [simp]: "quot_to_fract (quot_of_fract x) = x"
-  unfolding quot_to_fract_def
-proof transfer
-  fix x :: "'a \<times> 'a" assume rel: "fractrel x x"
-  define x' where "x' = normalize_quot x"
-  obtain a b where [simp]: "x = (a, b)" by (cases x)
-  from rel have "b \<noteq> 0" by simp
-  from normalize_quotE[OF this, of a] guess d .
-  hence "a = fst x' * d" "b = snd x' * d" "d \<noteq> 0" "snd x' \<noteq> 0" by (simp_all add: x'_def)
-  thus "fractrel (case x' of (a, b) \<Rightarrow> if b = 0 then (0, 1) else (a, b)) x"
-    by (auto simp add: case_prod_unfold)
-qed
-
-lemma quot_of_fract_quot_to_fract: "quot_of_fract (quot_to_fract x) = normalize_quot x"
-proof (cases "snd x = 0")
-  case True
-  thus ?thesis unfolding quot_to_fract_def
-    by transfer (simp add: case_prod_unfold normalize_quot_def)
-next
-  case False
-  thus ?thesis unfolding quot_to_fract_def by transfer (simp add: case_prod_unfold)
-qed
-
-lemma quot_of_fract_quot_to_fract': 
-  "x \<in> normalized_fracts \<Longrightarrow> quot_of_fract (quot_to_fract x) = x"
-  unfolding quot_to_fract_def by transfer (auto simp: normalize_quot_id)
-
-lemma quot_of_fract_in_normalized_fracts [simp]: "quot_of_fract x \<in> normalized_fracts"
-  by transfer simp
-
-lemma normalize_quotI:
-  assumes "a * d = b * c" "b \<noteq> 0" "(c, d) \<in> normalized_fracts"
-  shows   "normalize_quot (a, b) = (c, d)"
-proof -
-  from assms have "normalize_quot (a, b) = normalize_quot (c, d)"
-    by (subst normalize_quot_eq_iff) auto
-  also have "\<dots> = (c, d)" by (intro normalize_quot_id) fact
-  finally show ?thesis .
-qed
-
-lemma td_normalized_fract:
-  "type_definition quot_of_fract quot_to_fract normalized_fracts"
-  by standard (simp_all add: quot_of_fract_quot_to_fract')
-
-lemma quot_of_fract_add_aux:
-  assumes "snd x \<noteq> 0" "snd y \<noteq> 0" 
-  shows   "(fst x * snd y + fst y * snd x) * (snd (normalize_quot x) * snd (normalize_quot y)) =
-             snd x * snd y * (fst (normalize_quot x) * snd (normalize_quot y) +
-             snd (normalize_quot x) * fst (normalize_quot y))"
-proof -
-  from normalize_quotE'[OF assms(1)] guess d . note d = this
-  from normalize_quotE'[OF assms(2)] guess e . note e = this
-  show ?thesis by (simp_all add: d e algebra_simps)
-qed
-
-
-locale fract_as_normalized_quot
-begin
-setup_lifting td_normalized_fract
-end
-
-
-lemma quot_of_fract_add:
-  "quot_of_fract (x + y) = 
-     (let (a,b) = quot_of_fract x; (c,d) = quot_of_fract y
-      in  normalize_quot (a * d + b * c, b * d))"
-  by transfer (insert quot_of_fract_add_aux, 
-               simp_all add: Let_def case_prod_unfold normalize_quot_eq_iff)
-
-lemma quot_of_fract_uminus:
-  "quot_of_fract (-x) = (let (a,b) = quot_of_fract x in (-a, b))"
-  by transfer (auto simp: case_prod_unfold Let_def normalize_quot_def dvd_neg_div mult_unit_dvd_iff)
-
-lemma quot_of_fract_diff:
-  "quot_of_fract (x - y) = 
-     (let (a,b) = quot_of_fract x; (c,d) = quot_of_fract y
-      in  normalize_quot (a * d - b * c, b * d))" (is "_ = ?rhs")
-proof -
-  have "x - y = x + -y" by simp
-  also have "quot_of_fract \<dots> = ?rhs"
-    by (simp only: quot_of_fract_add quot_of_fract_uminus Let_def case_prod_unfold) simp_all
-  finally show ?thesis .
-qed
-
-lemma normalize_quot_mult_coprime:
-  assumes "coprime a b" "coprime c d" "unit_factor b = 1" "unit_factor d = 1"
-  defines "e \<equiv> fst (normalize_quot (a, d))" and "f \<equiv> snd (normalize_quot (a, d))"
-     and  "g \<equiv> fst (normalize_quot (c, b))" and "h \<equiv> snd (normalize_quot (c, b))"
-  shows   "normalize_quot (a * c, b * d) = (e * g, f * h)"
-proof (rule normalize_quotI)
-  from assms have "b \<noteq> 0" "d \<noteq> 0" by auto
-  from normalize_quotE[OF \<open>b \<noteq> 0\<close>, of c] guess k . note k = this [folded assms]
-  from normalize_quotE[OF \<open>d \<noteq> 0\<close>, of a] guess l . note l = this [folded assms]
-  from k l show "a * c * (f * h) = b * d * (e * g)" by (simp_all)
-  from assms have [simp]: "unit_factor f = 1" "unit_factor h = 1"
-    by simp_all
-  from assms have "coprime e f" "coprime g h" by (simp_all add: coprime_normalize_quot)
-  with k l assms(1,2) show "(e * g, f * h) \<in> normalized_fracts"
-    by (simp add: normalized_fracts_def unit_factor_mult coprime_mul_eq coprime_mul_eq')
-qed (insert assms(3,4), auto)
-
-lemma normalize_quot_mult:
-  assumes "snd x \<noteq> 0" "snd y \<noteq> 0"
-  shows   "normalize_quot (fst x * fst y, snd x * snd y) = normalize_quot 
-             (fst (normalize_quot x) * fst (normalize_quot y),
-              snd (normalize_quot x) * snd (normalize_quot y))"
-proof -
-  from normalize_quotE'[OF assms(1)] guess d . note d = this
-  from normalize_quotE'[OF assms(2)] guess e . note e = this
-  show ?thesis by (simp_all add: d e algebra_simps normalize_quot_eq_iff)
-qed
-
-lemma quot_of_fract_mult:
-  "quot_of_fract (x * y) = 
-     (let (a,b) = quot_of_fract x; (c,d) = quot_of_fract y;
-          (e,f) = normalize_quot (a,d); (g,h) = normalize_quot (c,b)
-      in  (e*g, f*h))"
-  by transfer (simp_all add: Let_def case_prod_unfold normalize_quot_mult_coprime [symmetric]
-                 coprime_normalize_quot normalize_quot_mult [symmetric])
-  
-lemma normalize_quot_0 [simp]: 
-    "normalize_quot (0, x) = (0, 1)" "normalize_quot (x, 0) = (0, 1)"
-  by (simp_all add: normalize_quot_def)
-  
-lemma normalize_quot_eq_0_iff [simp]: "fst (normalize_quot x) = 0 \<longleftrightarrow> fst x = 0 \<or> snd x = 0"
-  by (auto simp: normalize_quot_def case_prod_unfold Let_def div_mult_unit2 dvd_div_eq_0_iff)
-  find_theorems "_ div _ = 0"
-  
-lemma fst_quot_of_fract_0_imp: "fst (quot_of_fract x) = 0 \<Longrightarrow> snd (quot_of_fract x) = 1"
-  by transfer auto
-
-lemma normalize_quot_swap:
-  assumes "a \<noteq> 0" "b \<noteq> 0"
-  defines "a' \<equiv> fst (normalize_quot (a, b))" and "b' \<equiv> snd (normalize_quot (a, b))"
-  shows   "normalize_quot (b, a) = (b' div unit_factor a', a' div unit_factor a')"
-proof (rule normalize_quotI)
-  from normalize_quotE[OF assms(2), of a] guess d . note d = this [folded assms(3,4)]
-  show "b * (a' div unit_factor a') = a * (b' div unit_factor a')"
-    using assms(1,2) d 
-    by (simp add: div_unit_factor [symmetric] unit_div_mult_swap mult_ac del: div_unit_factor)
-  have "coprime a' b'" by (simp add: a'_def b'_def coprime_normalize_quot)
-  thus "(b' div unit_factor a', a' div unit_factor a') \<in> normalized_fracts"
-    using assms(1,2) d by (auto simp: normalized_fracts_def gcd_div_unit1 gcd_div_unit2 gcd.commute)
-qed fact+
-  
-lemma quot_of_fract_inverse:
-  "quot_of_fract (inverse x) = 
-     (let (a,b) = quot_of_fract x; d = unit_factor a 
-      in  if d = 0 then (0, 1) else (b div d, a div d))"
-proof (transfer, goal_cases)
-  case (1 x)
-  from normalize_quot_swap[of "fst x" "snd x"] show ?case
-    by (auto simp: Let_def case_prod_unfold)
-qed
-
-lemma normalize_quot_div_unit_left:
-  fixes x y u
-  assumes "is_unit u"
-  defines "x' \<equiv> fst (normalize_quot (x, y))" and "y' \<equiv> snd (normalize_quot (x, y))"
-  shows "normalize_quot (x div u, y) = (x' div u, y')"
-proof (cases "y = 0")
-  case False
-  from normalize_quotE[OF this, of x] guess d . note d = this[folded assms(2,3)]
-  from assms have "coprime x' y'" "unit_factor y' = 1" by (simp_all add: coprime_normalize_quot)
-  with False d \<open>is_unit u\<close> show ?thesis
-    by (intro normalize_quotI)
-       (auto simp: normalized_fracts_def unit_div_mult_swap unit_div_commute unit_div_cancel
-          gcd_div_unit1)
-qed (simp_all add: assms)
-
-lemma normalize_quot_div_unit_right:
-  fixes x y u
-  assumes "is_unit u"
-  defines "x' \<equiv> fst (normalize_quot (x, y))" and "y' \<equiv> snd (normalize_quot (x, y))"
-  shows "normalize_quot (x, y div u) = (x' * u, y')"
-proof (cases "y = 0")
-  case False
-  from normalize_quotE[OF this, of x] guess d . note d = this[folded assms(2,3)]
-  from assms have "coprime x' y'" "unit_factor y' = 1" by (simp_all add: coprime_normalize_quot)
-  with False d \<open>is_unit u\<close> show ?thesis
-    by (intro normalize_quotI)
-       (auto simp: normalized_fracts_def unit_div_mult_swap unit_div_commute unit_div_cancel
-          gcd_mult_unit1 unit_div_eq_0_iff mult.assoc [symmetric])
-qed (simp_all add: assms)
-
-lemma normalize_quot_normalize_left:
-  fixes x y u
-  defines "x' \<equiv> fst (normalize_quot (x, y))" and "y' \<equiv> snd (normalize_quot (x, y))"
-  shows "normalize_quot (normalize x, y) = (x' div unit_factor x, y')"
-  using normalize_quot_div_unit_left[of "unit_factor x" x y]
-  by (cases "x = 0") (simp_all add: assms)
-  
-lemma normalize_quot_normalize_right:
-  fixes x y u
-  defines "x' \<equiv> fst (normalize_quot (x, y))" and "y' \<equiv> snd (normalize_quot (x, y))"
-  shows "normalize_quot (x, normalize y) = (x' * unit_factor y, y')"
-  using normalize_quot_div_unit_right[of "unit_factor y" x y]
-  by (cases "y = 0") (simp_all add: assms)
-  
-lemma quot_of_fract_0 [simp]: "quot_of_fract 0 = (0, 1)"
-  by transfer auto
-
-lemma quot_of_fract_1 [simp]: "quot_of_fract 1 = (1, 1)"
-  by transfer (rule normalize_quotI, simp_all add: normalized_fracts_def)
-
-lemma quot_of_fract_divide:
-  "quot_of_fract (x / y) = (if y = 0 then (0, 1) else
-     (let (a,b) = quot_of_fract x; (c,d) = quot_of_fract y;
-          (e,f) = normalize_quot (a,c); (g,h) = normalize_quot (d,b)
-      in  (e * g, f * h)))" (is "_ = ?rhs")
-proof (cases "y = 0")
-  case False
-  hence A: "fst (quot_of_fract y) \<noteq> 0" by transfer auto
-  have "x / y = x * inverse y" by (simp add: divide_inverse)
-  also from False A have "quot_of_fract \<dots> = ?rhs"
-    by (simp only: quot_of_fract_mult quot_of_fract_inverse)
-       (simp_all add: Let_def case_prod_unfold fst_quot_of_fract_0_imp
-          normalize_quot_div_unit_left normalize_quot_div_unit_right 
-          normalize_quot_normalize_right normalize_quot_normalize_left)
-  finally show ?thesis .
-qed simp_all
-
-end